Do 45/225 and simplify and that’s your answer
Answer:
x=-6, y=1
Step-by-step explanation:
Let's solve your system by substitution.
y=x+7;−2x−11=y
Step: Solve y=x+7 for y:
y=x+7
Step: Substitute x+7 for y in −2x−11=y:
−2x−11=y
−2x−11=x+7
−2x−11+−x=x+7+−x(Add -x to both sides)
−3x−11=7
−3x−11+11=7+11(Add 11 to both sides)
−3x=18
−3x/
−3
=
18/
−3 (Divide both sides by -3)
x=−6
Step: Substitute−6 for x in y=x+7:
y=x+7
y=−6+7
y=1 (Simplify both sides of the equation)
Answer:
x=−6 and y=1
Answer:
(x-6) (x-4)
Step-by-step explanation:
x^2 - 10x + 24
What two number multiply to 24 and add to -10
-6*-4 = 24
-6+-4 = -10
(x-6) (x-4)